THE SOCIO-ECONOMIC BENEFITS OF MICROFINANCE: CONVENTIONAL VS. ISLAMIC - Amela Trokic; Eldina Barakovac; Velid Efendic (Journal of Islamic Monetary Economics and Finance, 2020)
The reduction of poverty and socio-economic development has become a foremost issue in modern society. One approach to improving this was the establishment of microfinance, which has since become an important part of poverty alleviation strategies, but very few studies have considered its benefits based on characteristics other than poverty. Therefore, this study aims to investigate and determine how different client characteristics affect the way people benefit from the financing provided by microfinance institutions. Data were gathered from the beneficiaries of both conventional and Islamic microfinance using a questionnaire, and then analysed using the Kruskal-Wallis and the Mann–Whitney U tests. The results show how MFI financing benefits clients differently based on certain characteristics, as well as how these socioeconomic benefits differ based on whether the financing is provided by a conventional or an Islamic MFI. Overall, conventional and Islamic MFIs have similar strategies when it comes to providing socio-economic benefits to their clients. However, where they diverge is when client gender is considered, as IMFIs are more likely to benefit women. This research will be beneficial to MFIs in terms of the development of their services, as it will help them identify the strengths and weaknesses of their offerings and how well these are able to assist them in fulfilling their purpose of providing benefit to the poorest of the poor, increasing financial inclusion and contributing to socio-economic development.